Modelling Sustainable Port Operations: Balancing Inputs and Outputs with the Cobb–Douglas Function - Derpich-Contreras, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This research presents a comprehensive analysis of sustainable port operations in two countries, utilizing econometric models, including the stochastic frontier and Cobb–Douglas models, to examine critical elements such as the number of empty containers and vessel traffic. These factors, driven by globalization, significantly impact the environmental and social dynamics within port operations. By integrating these models, this study assesses efficiency and sustainability, addressing methodological gaps in existing research, particularly in the quantification and generalization of CO2 emissions. Findings indicate that, despite differences in port management and operations, CO2 levels can be estimated using operational variables without the need for complete CO2 traceability throughout the logistics chain. This study concludes by emphasizing the importance of incorporating international environmental standards into port operations and recommends the use of econometric models as tools for assessing and managing port sustainability effectively. © 2024 by the authors.